Development of flood vulnerability curves for the components and contents of low-rise residential buildings - Ong, Ralph Aldrin Y.
According to the Citizens' Disaster Response Center (CDRC, 2012), flooding is the top natural disaster in the Philippines. Despite this fact, flood damage costs are not properly estimated in the country. Hence, people are unaware of how vulnerable their houses are to floods. This study addresses the problem through a three-step procedure: 1) characterization of the components and contents of low-rise residential buildings, 2) determination of the flood sensitivity of these components and contents, and 3) development of flood vulnerability curves for the six categories of low-rise residential buildings- one-storey (low-end, middle class, and high-end) and two-storey (low-end, middle class, and high-end) buildings. Field surveys were carried out in order to characterize the building components and contents as well as to estimate the value of damages. After the typical components and contents were identified, flood sensitivity was determined. Results show that residential buildings with low-end finish are the most vulnerable to flood inundation mainly due to their structural components, i.e. wall partitions made of plywood/plyboard, that have a high flood sensitivity factor. Generally, building components are the major indicator of a residential building's vulnerability to flood. The vulnerability of building contents greatly depends on their location within the building. Hence, changing room heights, elevations, and configurations would have significant effects on their vulnerability.